Foundations of SQL Server 2005 Business Intelligence - Langit, Lynn (Apress : Imprint: Apress, 2007)
Just as every business needs to effectively employ business intelligence (BI) to stay competitive, every IT professional needs to master BI to stay employed in this fastest-growing segment of information technology. Foundations of SQL Server 2005 Business Intelligence is the quickest path to understanding BI, and it is essential reading for all who work with SQL Server 2005. It is written from a practical perspective, perfect for anyone who uses the tools in SQL Server 2005s extraordinarily rich BI product suite. This book explains how best to use Analysis Services, SQL Server Integration Services, SQL Server Reporting Services, and SQL Server Data Mining. It also describes best practices for implementing end-to-end BI solutions in small, medium, and large business environments. And it provides important information about integrating BI with various client tools, including Excel, Business Scorecards, Proclarity, and SharePoint Portal Server. Developers, end users, and even managers will find this an enlightening guide to the power and promise of SQL Server 2005 BI.